1979
DOI: 10.1111/j.1432-1033.1979.tb13090.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of a Hitherto‐Unknown Enzyme Reducing the Carbon‐Carbon Double Bond of α,β‐Unsaturated Carboxylate Anions

Abstract: 2‐Enoate‐reductase, a previously unknown soluble enzyme is present in Clostridium kluyveri and another Clostridium species growing on (E)‐2‐butenoate. From the latter the reductase was purified 88‐fold with an overall yield up to 74%. The enzyme was pure as judged by polyacrylamide gel electrophoresis with and without sodium dodecyl sulphate as well as by isoelectric focusing. The purification of the enzyme was performed in the presence of (E)‐2‐methyl‐2‐butenoate as substrate to keep the enzyme in the oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…In an analogy to a reaction mechanism suggested for an enzyme (EC 1.3.1.31) reducing the carbon-carbon double bond of ␣,␤-unsaturated carboxylate anions of the methylbutenoate or cinnamate type (16), which also eliminate halide from the double bond (14), we propose that the following mechanism could play a role in the enzyme-catalyzed dehalogenation of maleylacetates when the substrate is used in the form of hydroxymuconate (Fig. 5A [the numbering of carbon has been made uniform for hydroxymuconate and maleylacetate to facilitate the discussion]).…”
Section: Discussionmentioning
confidence: 99%
“…In an analogy to a reaction mechanism suggested for an enzyme (EC 1.3.1.31) reducing the carbon-carbon double bond of ␣,␤-unsaturated carboxylate anions of the methylbutenoate or cinnamate type (16), which also eliminate halide from the double bond (14), we propose that the following mechanism could play a role in the enzyme-catalyzed dehalogenation of maleylacetates when the substrate is used in the form of hydroxymuconate (Fig. 5A [the numbering of carbon has been made uniform for hydroxymuconate and maleylacetate to facilitate the discussion]).…”
Section: Discussionmentioning
confidence: 99%
“…We described enoate reductase a conjugated Fe-S flavoprotein which reduces nonactivated (II, P-unsaturated carboxylates in a NADH-dependent reaction [6]. The source was C. La 1 a non-proteolytic clostridium grown on (E)-2-butenoate.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that cell extracts of C. kluyveri catalyze the stereospecific reduction of a wide variety of ␣,␤-unsaturated fatty acids with H 2 . In the genome of C. kluyveri nine CDS for enoate reductases are found, only one of which (CKL 0743) has been characterized (45,46). The physiological function of the enoate reductases is not known with certainty.…”
Section: Ethanol Dehydrogenases and Acetaldehyde Dehydrogenases In Amentioning
confidence: 99%